Pemberian Nafkah Iddah dan Mut'ah pada Perkara Cerai Talak di Pengadilan Agama Surabaya (Studi Putusan Nomor 3628/Pdt.G/2024/PA.Sby) - Putri, Rismalidiana; Ahmad, Moh Jufri (Journal Evidence Of Law, 2024)
The purpose of this study is to identify the forms of legal protection for wives and children in divorce cases, particularly regarding talaq divorce, and to analyze the provision of iddah and mut'ah support. The research uses a juridical approach based on laws governing iddah and mut'ah support, as well as the Compilation of Islamic Law. Iddah support is a financial obligation provided during the iddah period, while mut'ah support is given as a form of respect and compensation for divorce. Although regulated under Law Number 16 of 2019, which amended Law Number 1 of 1974 on Marriage, and the Compilation of Islamic Law, there is no specific regulation determining the amount of such support. In practice, courts may set the support amount based on the husband’s financial capacity and other relevant factors. This qualitative field research was conducted at the Surabaya Religious Court, focusing on the Surabaya Religious Court Decision Number 3628/Pdt.G/2024/PA.Sby. The study reveals that the provision of iddah and mut'ah support in the decision was based on Article 149 letters a and b of the Compilation of Islamic Law, with the amount determined by the husband’s financial capacity and the judge’s assessment during the trial.